Cam Jansen and the mystery of the television dog - Adler, David A.; local (New York : Puffin, 2004)
Fifth-grader Cam uses her photographic memory, with help from her friend Eric and his twin sisters, to solve the mystery of Poochie, a famo
us canine television star.
Keywords: sears; Mystery and detective stories; sears; sears